Retos de la Filosofía del Derecho y de los derechos humanos a propósito de la obra de Carla Faralli - Pérez Montero, María Eugenia (Anuario de Derechos Humanos. Nueva Época, 2009)
The main target of this work is to show the development nowadays of the philosophical speech about the iuspositivism model crisis according to British Law Philosopher H.L.A Hart following Carla Faralli’s work as an inexcusable reference in any investigation related to the current situation of the Philosophy of Law which is very close to the enquiries stated by the ethical dilemmas which are causing quick and new advances in biomedicine, multicultural consequences as well as the contribution and impact of new technologies and its regulation.
Keywords: Philosophy of Law; Human Rights; Ethics; Bioethics; Multiculturalism; New Technologies